2013
DOI: 10.1002/jmri.24039
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and limitations of diffusion tensor imaging metrics in the cervical spinal cord in neurologically intact subjects

Abstract: This study provides DTI data for GM and WM funiculi throughout the CSC. While DTI metrics may be used to define cord pathology, variations in metrics due to age and signal quality need to be accounted for before making definitive conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
28
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 35 publications
4
28
1
Order By: Relevance
“…We observed that the FA and ADC values indicated significant differences between GM and individual WM funiculi. These data are supported by previous studies [1,21]. In addition, we found that there were significant differences in the FA and ADC values of the different WM funiculi at different CSC segments, but that there were no differences in the DTI parameters of the GM from different CSC segments, an analysis that was not performed by Vedantam et al Compared with the upper and middle segments, both FA and ADC values from WM funiculis of lower segments were lower.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…We observed that the FA and ADC values indicated significant differences between GM and individual WM funiculi. These data are supported by previous studies [1,21]. In addition, we found that there were significant differences in the FA and ADC values of the different WM funiculi at different CSC segments, but that there were no differences in the DTI parameters of the GM from different CSC segments, an analysis that was not performed by Vedantam et al Compared with the upper and middle segments, both FA and ADC values from WM funiculis of lower segments were lower.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, we found that there were significant differences in the FA and ADC values of the different WM funiculi at different CSC segments, but that there were no differences in the DTI parameters of the GM from different CSC segments, an analysis that was not performed by Vedantam et al Compared with the upper and middle segments, both FA and ADC values from WM funiculis of lower segments were lower. These results could be due to the decreased spinal cord volume of the lower segments, or to differences in signal-to-noise ratio (SNR) across the cervical segments [1,11,21].…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations